2006
DOI: 10.1126/science.1133822
|View full text |Cite
|
Sign up to set email alerts
|

The Heartbeat of the Oligocene Climate System

Abstract: A 13-million-year continuous record of Oligocene climate from the equatorial Pacific reveals a pronounced “heartbeat” in the global carbon cycle and periodicity of glaciations. This heartbeat consists of 405,000-, 127,000-, and 96,000-year eccentricity cycles and 1.2-million-year obliquity cycles in periodically recurring glacial and carbon cycle events. That climate system response to intricate orbital variations suggests a fundamental interaction of the carbon cycle, solar forcing, and glacial events. Box mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
661
3
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 604 publications
(740 citation statements)
references
References 30 publications
46
661
3
3
Order By: Relevance
“…Superimposed on the above long-term swings in the δ 18 O Oligocene record, fluctuations on timescales shorter than several 120 Myr were identified in the high-resolution record from ODP 1218 (Pälike et al, 2006). These fluctuations in periods of 405 kyr and 1.2 Myr are related to Earth's orbital variations in eccentricity and obliquity, respectively and have been referred as the short-term "heartbeat" of the Oligocene climate (Pälike et al, 2006). Oligocene records close to Antarctica are needed to better resolve Antarctic ice sheet and paleoceanographic configurations and variations at different timescales and 125 under scenarios of increasing atmospheric CO 2 values and δ 18 O records, which imply a climatic warming and/or ice volume loss.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Superimposed on the above long-term swings in the δ 18 O Oligocene record, fluctuations on timescales shorter than several 120 Myr were identified in the high-resolution record from ODP 1218 (Pälike et al, 2006). These fluctuations in periods of 405 kyr and 1.2 Myr are related to Earth's orbital variations in eccentricity and obliquity, respectively and have been referred as the short-term "heartbeat" of the Oligocene climate (Pälike et al, 2006). Oligocene records close to Antarctica are needed to better resolve Antarctic ice sheet and paleoceanographic configurations and variations at different timescales and 125 under scenarios of increasing atmospheric CO 2 values and δ 18 O records, which imply a climatic warming and/or ice volume loss.…”
Section: Introductionmentioning
confidence: 92%
“…Based on the study of the isotopic record in sediments from the Atlantic, the Indian and the equatorial Pacific, Pekar et al (2006) explained the conundrum of a glaciated Antarctica, and varying intrabasinal δ 18 O values with the coeval existence of two deep-water masses, one sourced from Antarctica and another, warmer bottom-water, sourced from lower latitudes. Superimposed on the above long-term swings in the δ 18 O Oligocene record, fluctuations on timescales shorter than several 120 Myr were identified in the high-resolution record from ODP 1218 (Pälike et al, 2006). These fluctuations in periods of 405 kyr and 1.2 Myr are related to Earth's orbital variations in eccentricity and obliquity, respectively and have been referred as the short-term "heartbeat" of the Oligocene climate (Pälike et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this case climatic variations influence the transfer of the detrital argillaceous fraction, coming from the platform top or the adjacent continental areas, and the carbonate sedimentation, which is constituted by benthic, pelagic, or winnowed platform top material. It was already shown that the lithological variations, induced by the variations of the Earth's orbit parameters in the MILANKOVITCH band (periods from 20 to 400 kyr; BERGER, 1978aBERGER, , 1978bLASKAR, 1988;BERGER & LOUTRE, 1991;LASKAR et al, 2004LASKAR et al, , 2011 were appropriate to establish a very precise time scale (e.g., HERBERT & D'HONDT, 1990;ten KATE & SPRENGER, 1993;HILGEN et al, 1993HILGEN et al, , 1999HOU-SE & GALE, 1995;HERBERT, 1999;SHACKLETON et al, 1999;CLEMENS, 1999;HINNOV, 2000HINNOV, , 2005PÄLIKE et al, 2001;GALEOTTI et al, 2003;HENNE-BERT & DUPUIS, 2003;DINARÈS-TURELL et al, 2003;LOURENS et al, 2005aLOURENS et al, , 2005bFIET et al, 2006;PÄLIKE et al, 2006;SPROVIERI et al, 2006;HINNOV & OGG, 2007;WESTERHOLD et al, 2007WESTERHOLD et al, , 2008HENNEBERT et al, 2009;HENNEBERT, 2012).…”
Section: Astrochronologymentioning
confidence: 99%